Ginsenoside Rg1-Notoginsenoside R1-Protocatechuic Aldehyde Reduces Atherosclerosis and Attenuates Low-Shear Stress-Induced Vascular Endothelial Cell Dysfunction - Zhang, Lei; Li, Yuan; Ma, Xin; Liu, Jiali; Wang, Xiaojie; Zhang, Lingxiao; Li, Chao; Li, Yunlun; Yang, Wenqing (Frontiers in Pharmacology, 2021)
Background: The Fufang Danshen formula is widely used in traditional Chinese medicine for the clinical treatment of coronary heart disease. However, there is no literature reporting the anti-atherosclerotic effect and mechanism of its combination of active ingredients, namely Ginsenoside Rg1-Notoginsenoside R1-Protocatechuic aldehyde (RRP). The aim of this study was to investigate the anti-atherosclerotic effects in ApoE-/- mice and potential mechanism of RRP in low shear stress-injured vascular endothelial cell. Methods: In vivo assay, ApoE-/-mice were randomly divided into three groups: model group, Rosuvastatin group, and RRP group, with C57BL/6J mice as control group. A variety of staining methods were utilized for the observation of aortic plaque. The changes of the blood lipid indexes were observed by an automatic biochemistry analyzer. ET-1, eNOS, TAX2, and PGI2 were analyzed by enzymelinked immunosorbent assay. In vitro, we used fluid shear system to induce cell injury and silenced Piezo1 expression in HUVECs by siRNA. We observed the morphological, proliferation, migration and tube formation activity changes of cells after RRP intervention. Quantitative Real-Time PCR and western blot analysis was applied to observe m RNA and protein expression. Results: Results showed that RRP treatment reduced atherosclerotic area and lipid level and improved endothelial function in ApoE-/- mice. RRP significantly repaired cell morphology, reduced cell excessive proliferation and ameliorated migration and tube formation activity. In addition, we found that RRP could affect FAK-PI3K/Akt signaling pathways. Importantly, Piezo1 siRNA abolished the protection effects of RRP. Conclusions: In summary, our results suggested that RRP ameliorated atherosclerotic plaque formation and endothelial cell injury by intervening the FAK-PI3K/Akt signaling pathways. Piezo1 is a possible target of RRP in the treatment of atherosclerosis. These results indicate that RRP may be apotential drug for atherosclerosis.